Geotechnical engineering for transportation infrastructure theory and practice, planning and design, construction and maintenance : proceedings of the Twelfth European Conference on Soil Mechanics and Geotechnical Engineering, Amsterdam, Netherlands, 7-10 June 1999 : additional volume - Barendsm F.B (A.A. Balkema, 2000)
"Cities are growing, living standards improving; communication facilities develop rapidly, but physical mobility can't keep up. Transport by air, over water, rail, or road, above or underground, need drastic improvement. This appeal became the main theme at the XIIth European Conference on Soil Mechanics and Geotechnical Engineering held in Amsterdam, June 1999. The transportation infrastructure depends strongly on available geotechnical engineering capabilities. Therefore special emphasis is given to relevant large and complex projects, in design, under construction, or recently completed, so as to provide a realistic reference framework for technical, environmental, legislative, social, logistic, and economic questions and resolutions. These proceedings testify the readiness of the geotechnical engineering profession to meet future challenges."--BOOK JACKET.